The Development of Physics Students’ Worksheets Based on Science Process Skills in Basic Physics Course At Flores University - Yasinta Embu Ika; Hamsa Doa (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the feasibility level of physics worksheets and to figure out the increase on student’s understanding after using the physics worksheets based on science process skills. This study is a development research employing ADDIE development model which consists of five stages, namely: analysis, design, development, and implementation. The design of this study was One Group Pretest-Posttest Design. The instruments used were validity assessment sheet, feasibility assessment sheet, questionnaire about the students’ response toward the worksheets based on science process skills, and assessment of science process skills. the data were analyzed by using percentage of agreement (R), and N-gain (g). The results showed that the physics students’ worksheet based on science process skills was feasible and could be used in learning as the feasibility level reached 97%. The students’ understanding of fluid material gained through working with the worksheets can improve students’ science process skills both at the basic level and at the integrated level. This is proven by the results of the initial test or pre-test which indicate that the students' science process skills affected the learning outcomes obtained in which 62.25% of students’ scores were in good category and 35.75% of students’ scores were in fair category. Meanwhile, in the final test or post-test of students' science process skills, it was obtained that 74.50% of students’ scores were in very good category and 25.50% of students’ scores were in the fair category. This means that there is an increase by 0.7 % in students' science process skills when using the students’ worksheets.